2014
DOI: 10.1108/jadee-02-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Competitive forces and innovation strategies: a study of the Indonesian crab industries

Abstract: Purpose – The purpose of this paper is to evaluate the strengths and weaknesses of the current competitive position and performance of Indonesian Crab Industries (ICI). The paper examines whether a reorientation of the innovation strategic vision is needed to build future industrial excellence. Design/methodology/approach – Data collected from secondary sources and interviews with processors and stakeholders in the major ICI are analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…The second methodological implication concerns the measurement of market innovation in the context of rural Uganda, consistently with the most surprising empirical finding of this studythat market innovation is more likely to decrease when farmers are more innovative and have more access to labor. This seems to clash with earlier literature suggesting that access to human capital and innovativeness may drive, among other factors, market innovations (Yusuf and Trondsen, 2014;Kyomugisha et al, 2017). It is plausible that the interviewed Ugandan farmers may have perceived the formulation of this itemadapted from Johne (1999) in a Western, non-rural socio-economic contextas something not necessarily desirable, or even undesirable, in relation to market performance.…”
Section: Methodological Implicationscontrasting
confidence: 55%
“…The second methodological implication concerns the measurement of market innovation in the context of rural Uganda, consistently with the most surprising empirical finding of this studythat market innovation is more likely to decrease when farmers are more innovative and have more access to labor. This seems to clash with earlier literature suggesting that access to human capital and innovativeness may drive, among other factors, market innovations (Yusuf and Trondsen, 2014;Kyomugisha et al, 2017). It is plausible that the interviewed Ugandan farmers may have perceived the formulation of this itemadapted from Johne (1999) in a Western, non-rural socio-economic contextas something not necessarily desirable, or even undesirable, in relation to market performance.…”
Section: Methodological Implicationscontrasting
confidence: 55%
“…In recent years, many NGOs have developed their capacity for facilitating events, and some have further developed their capacities for innovation brokerage. Essential knowledge, attitudes, and skills for brokering innovation processes remain scarce in most agricultural research organizations, highlighting the need for investments in capacity development, if agricultural research organizations are to play useful roles in facilitating the work of platforms (Horton, 2012; Yusuf and Trondsen, 2014). Professionals based at a number of international and national R&D organizations have recently prepared a set of guidelines for designing, budgeting, and implementing successful innovation platforms (Schut et al , 2017).…”
Section: Emerging Themes and Policy Implicationsmentioning
confidence: 99%
“…In the Australian grains and oilseeds sectors, O'Donnell et al (2007) found that processors exercise monopoly and oligopsony toward consumers and producers. The study of Birthal et al (2019) concluded that the downstream market power of onion production is one of the major factors causing high price volatility in the onion market in India Yusuf and Trondsen (2014),. on the other hand, revealed that market power, in forms of access barriers, weakened competition in the Indonesian crab industry.…”
Section: Literature Reviewmentioning
confidence: 99%